2018
DOI: 10.1145/3093239
|View full text |Cite
|
Sign up to set email alerts
|

Subtree Isomorphism Revisited

Abstract: The Subtree Isomorphism problem asks whether a given tree is contained in another given tree. The problem is of fundamental importance and has been studied since the 1960s. For some variants, e.g., ordered trees , near-linear time algorithms are known, but for the general case truly subquadratic algorithms remain elusive. Our first result is a reduction from the Orthogonal Vectors problem to Subtree Isomorphism, showing that a truly subquadra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
88
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(89 citation statements)
references
References 46 publications
1
88
0
Order By: Relevance
“…For example, the polynomial method [41] has allowed for superpolylogarithmic shavings for APSP, and more recently to two other problems that are more closely related to ours, namely Longest Common Substring [9], and Hamming Nearest Neighbors [10]. A natural open question [41,9,10] is whether these techniques can lead to an n 2 / log ω (1) n algorithm for Edit-Distance as well. The lower bound of Backurs and Indyk is not sufficient to address this question, and only a much faster n 2 /2 ω(log n/ log log n) would have been required to improve the current CNF-SAT algorithms.…”
Section: Evidence For Sethmentioning
confidence: 96%
See 4 more Smart Citations
“…For example, the polynomial method [41] has allowed for superpolylogarithmic shavings for APSP, and more recently to two other problems that are more closely related to ours, namely Longest Common Substring [9], and Hamming Nearest Neighbors [10]. A natural open question [41,9,10] is whether these techniques can lead to an n 2 / log ω (1) n algorithm for Edit-Distance as well. The lower bound of Backurs and Indyk is not sufficient to address this question, and only a much faster n 2 /2 ω(log n/ log log n) would have been required to improve the current CNF-SAT algorithms.…”
Section: Evidence For Sethmentioning
confidence: 96%
“…Williams showed that faster-than-trivial Circuit-SAT algorithms for many circuit classes C would imply interesting new lower bounds against that class [40,42]. Via this connection, and known reductions from certain circuit families to CNF formulas, it is possible to show that refuting SETH implies a new circuit lower bound [29]: E NP cannot be solved by linear-size series-parallel circuits 1 . However, this is a very weak lower bound consequence.…”
Section: Evidence For Sethmentioning
confidence: 96%
See 3 more Smart Citations